2017
DOI: 10.1371/journal.pone.0175368
|View full text |Cite
|
Sign up to set email alerts
|

A systematic identification and analysis of scientists on Twitter

Abstract: Metrics derived from Twitter and other social media—often referred to as altmetrics—are increasingly used to estimate the broader social impacts of scholarship. Such efforts, however, may produce highly misleading results, as the entities that participate in conversations about science on these platforms are largely unknown. For instance, if altmetric activities are generated mainly by scientists, does it really capture broader social impacts of science? Here we present a systematic approach to identifying and… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
129
0
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 134 publications
(140 citation statements)
references
References 37 publications
5
129
0
6
Order By: Relevance
“…Bill Nye, often referred to as 'The Science Guy' from his past public television show, has 5.8 million followers (@BillNye, 2019). Ke, Ahn, and Sugimoto (2017) examined Twitter lists and memberships using a snowballing technique to find users with identifying information fitting the U.S. Bureau of Labor Statistic's definition of scientist occupations, as well as Wikipedia lists of scientist careers. The researchers found 45,867 scientists using Twitter, with mathematical and physical scientists underrepresented and social scientists overrepresented on the platform (Ke, Ahn, & Sugimoto, 2017).…”
Section: Tweeting Sciencementioning
confidence: 99%
See 4 more Smart Citations
“…Bill Nye, often referred to as 'The Science Guy' from his past public television show, has 5.8 million followers (@BillNye, 2019). Ke, Ahn, and Sugimoto (2017) examined Twitter lists and memberships using a snowballing technique to find users with identifying information fitting the U.S. Bureau of Labor Statistic's definition of scientist occupations, as well as Wikipedia lists of scientist careers. The researchers found 45,867 scientists using Twitter, with mathematical and physical scientists underrepresented and social scientists overrepresented on the platform (Ke, Ahn, & Sugimoto, 2017).…”
Section: Tweeting Sciencementioning
confidence: 99%
“…Ke, Ahn, and Sugimoto (2017) examined Twitter lists and memberships using a snowballing technique to find users with identifying information fitting the U.S. Bureau of Labor Statistic's definition of scientist occupations, as well as Wikipedia lists of scientist careers. The researchers found 45,867 scientists using Twitter, with mathematical and physical scientists underrepresented and social scientists overrepresented on the platform (Ke, Ahn, & Sugimoto, 2017). They also found that more male than female scientists used the platform (Ke, Ahn, & Sugimoto, 2017).…”
Section: Tweeting Sciencementioning
confidence: 99%
See 3 more Smart Citations